2011
DOI: 10.1111/j.1600-065x.2011.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of commensal microbiota on immune cell subsets and inflammatory responses

Abstract: Billions of years of coevolution shaped the mutually beneficial relationships between metazoans and symbiotic commensal microorganisms. Commensal microorganisms profoundly affect the physiology of the host and provide the host with survival advantages in several ways, while they could also trigger pathogenic immune responses and threaten the well-being of the host. Recent advances in DNA sequencing technology enabled the analysis of commensal microbiota, and improvements in the techniques of culturing gut-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 117 publications
(155 reference statements)
1
65
0
1
Order By: Relevance
“…6 Dysbiosis in patients with IBD, reflecting a dominance of potentially pro-inflammatory pathogens or pathobionts 6,35 over antiinflammatory commensals, is thought to result in a shift of the immunological balance in the intestinal mucosa toward inflammation. 6,[38][39][40] It still remains unclear whether the observed dysbiotic changes in the microbiota of patients with IBD are primarily responsible for the activation of the immune system and subsequent inflammation or if they rather represent a consequence of colitis and diarrhea caused by altered bacterial growth conditions. 6,41 In our study, we could observe a reversal of some of the reported dysbiotic changes in the intestinal microbiota of patients with UC after FMT, including a marked decrease in Proteobacteria including Enterobacteriaceae, an increase in Bacteroidetes, and a trend towards an increase of Firmicutes including Lachnospiraceae.…”
Section: Discussionmentioning
confidence: 98%
“…6 Dysbiosis in patients with IBD, reflecting a dominance of potentially pro-inflammatory pathogens or pathobionts 6,35 over antiinflammatory commensals, is thought to result in a shift of the immunological balance in the intestinal mucosa toward inflammation. 6,[38][39][40] It still remains unclear whether the observed dysbiotic changes in the microbiota of patients with IBD are primarily responsible for the activation of the immune system and subsequent inflammation or if they rather represent a consequence of colitis and diarrhea caused by altered bacterial growth conditions. 6,41 In our study, we could observe a reversal of some of the reported dysbiotic changes in the intestinal microbiota of patients with UC after FMT, including a marked decrease in Proteobacteria including Enterobacteriaceae, an increase in Bacteroidetes, and a trend towards an increase of Firmicutes including Lachnospiraceae.…”
Section: Discussionmentioning
confidence: 98%
“…Many recent findings have focused on how commensal microbiota affects the immune cell subsets, such as regulatory T cells, Th17, Th1, and Th2; in addition, their close link has been explored in terms of inflammation. 20 In this study, we investigated the commensal bacteria-influenced immune balance by exploring the Th and Treg cells equilibrium in antibiotic-treated mice, a homeostasis of the hostmicrobiota mutualism. And from this research we speculated that dysbacteriosis aggravated inflammatory exudates in the lung tissues of mice after infection with FM1 viruses, thereby causing increased virus amplification in the lungs, disrupting the Th/ Treg immune balance in the body and increased the risk of inflammation in the body and disrupted the immune balance.…”
Section: Discussionmentioning
confidence: 99%
“…This seemingly elaborate mechanism ensures that the villi have more room for their primary function, uptake of nutrients and water, and that specific immune effector-cells can be initiated at one single site (after pathogen recognition) and then be evenly redistributed over the entire length of the gut, thereby providing uniform specific protection and memory. The entire process is critically controlled by dendritic cells and effector-cells are always under control of T regulator cells, ensuring not only a decent start of the specific response but also, and maybe more importantly, a timely end to the response (Wells, 2011) avoiding self-inflicted pathology (Chinen and Rudensky, 2012;Van Driel and Ang, 2008).…”
Section: Submucosal Effectsmentioning
confidence: 99%